2018
DOI: 10.2147/jpr.s178853
|View full text |Cite
|
Sign up to set email alerts
|

Impact of variation in physical activity after total joint replacement

Abstract: PurposePatients who undergo total knee arthroplasty (TKA) or total hip arthroplasty (THA) often develop postoperative pain. Exercise approaches are recommended postoperatively; however, the impact of excessive variation in physical activity is unclear. The purpose of the present preliminary study was to investigate the impact of excessive variation in physical activity using the accelerometer in the early period after TKA or THA.Patients and methodsSeventy-two patients were enrolled in the study. Forty patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Physical activity studies were consistent in the number of sensors implemented, with 21 studies (81%) using a single sensor for activity measurements 35–40 42 43 45–57. As technology and availability of wearable accelerometers has progressed, the type of sensor used has also changed.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…Physical activity studies were consistent in the number of sensors implemented, with 21 studies (81%) using a single sensor for activity measurements 35–40 42 43 45–57. As technology and availability of wearable accelerometers has progressed, the type of sensor used has also changed.…”
Section: Resultsmentioning
confidence: 85%
“…In studies published between 2008 and 2016, nine studies (69%)36 37 40 42 44 45 58–60 reported using a uniaxial accelerometer versus just three studies (23%)46 55 56 using a triaxial accelerometer. Conversely, in studies published in 2017–2019, eight studies (62%)35 38 47 49 50 53 54 57 reported using a triaxial accelerometer, while only three (23%)39 43 45 used a uniaxial accelerometer. Overall, three studies did not report the number of axes recorded,41 48 51 and most studies within this subgroup (73%)36 37 40–45 47 48 50–55 57 60 did not report the sampling rate at which data were collected.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations